Atividade turística como incentivo ao desenvolvimento local para o Vale do São Lourenço no Mato Grosso - Aguiar, Bárbarah Lucy Pinheiro de (2018)
The economic relations that permeate the globe have provided economic growth in an inhomogeneous way for societies. The universalization of productive processes for regions with distinct local characteristics has promoted peripheral regions. In this sense there is a need to work these regions with peculiar realities so that they can reach a level of development that meets their economic, social, cultural and environmental needs. The present study sought to work this theme in a geographical parameter that lives this reality of peripheral region, the Vale do São Lourenço. The Valley, because it has a regional reality that does not fit within the productive matrix of the State of Mato Grosso, exports of commodities in scale, found in tourism an alternative to work on local development. The tourist activity is configured as something that goes beyond the industry of services of visitation to tourist points. Tourism, when well planned, can function as an endogenous development tool for communities with available natural resources and diversified cultural training. Based on this reality, the research sought in Data Envelopment Analysis, the methodology to verify the efficiency of the tourism carried out in the Valley and to identify if the tourist activity has promoted the local development. According to the results, tourism activity has been concentrated in only one municipality of the Valley and tourism has presented itself with space for diversification and growth.